Estudo da influência dos parâmetros no processo de soldagem GMAW - arco pulsado - Alexander Fischer (2011)
Pulsed gas metal arc welding describes the metal transfer mode involving oscillation (pulsing) of the welding current from a high pulse current in which level drop growth, necking of wire tip and detachment occur, and a low background current, which is applied to maintain the arc.The advantages of the process are: metal transfer without spatter formation and a wide range of welding power. The disadvantages are: noise pollution (pulse frequency), the cost of the equipment is much higher and the process is slightly more complex as compared to standard GMAW because a number of variables are required to be controlled to achieve good results. This study investigated the effect of the weld polarity on the metal transfer at the pulsed GMAW process, the effect of arc self-regulation with the current modulation mode IP-UB, theinfluence of the base parameters at the metal transfer and the limits of application. Experiments were carried out on an automated GMAW platform. The base metal was mild steel ASTM-A36 with a thickness of 4mm and 2,5mm. The filler wire was ER70S-6 with a diameter of 1,2mm. It was used as shielding gas 82% argon with 18% CO2. During trials,a high speed camera was used to record the metal transfer process. During welding the arc voltage and the welding current were continuously measured and synchronized with the high speed images. The high speed camera used a sampling speed of 4000 frames per second (fps).The study of the metal transfer with different electrode polarities showed that a controlled metal transfer was only possible when the electrode is connected to the positive pole. The current modulation mode IP-UB demonstrated self regulation properties to maintain the arc length steady during welding. As advantages of this modulation mode where indentifiedthe constant droplet formation conditions during pulsing (constant current mode) and the self regulation effect during the base level (constant voltage mode). The study of the base parameters showed, the arc length was regulated with the base voltage, pulse duration and pulse current influenced the droplet formation and pulse frequency was coupled directly with the wire feed speed. At the low power level, the application of the pulsed GMAW process was limited by the lack of penetration and by the arc instability. At the high power level, the application was limitedby the high base voltage, what provoked during the different phases similar arc lengths.